Silicon Anode Material in the Form of Composite of functionalized graphene (FGO) and graphite nanoplatelets (GNPs) with silicon
Patent Information
- Application Number
- KR1020250024934
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-02-26
- Publication Date
- 2026-09-02
Smart Images

Figure PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a silicon anode material in which functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) are composited with silicon. Background Technology
[0003] Rechargeable batteries have established themselves as an essential technology in various industries, such as electric vehicles (EVs), energy storage systems (ESS), and portable electronic devices, serving as eco-friendly energy storage devices. Currently, graphite is primarily used as the anode material in commercially available rechargeable batteries, and graphite is classified into natural graphite and artificial graphite. However, graphite has limitations in meeting the demands for high-capacity batteries due to its structural characteristics and low theoretical capacity (372 mAh / g). In particular, natural graphite suffers from low structural stability due to volume expansion during long-term use, while artificial graphite has the disadvantage of requiring high costs due to complex manufacturing processes, such as high-temperature heat treatment. Accordingly, the development of next-generation anode materials capable of replacing graphite is essential.
[0004] Silicon is attracting attention as a next-generation anode material capable of providing more than 10 times the storage capacity of graphite, with a theoretical capacity of over 4200 mAh / g. In particular, silicon possesses high energy density and fast charge / discharge characteristics, and is expected to play an important role in the market requiring high-capacity lithium-ion batteries.
[0005] Accordingly, the silicon anode market is showing rapid growth and is projected to account for 10.1% of the total anode market by around 2027. Furthermore, the market size is expected to exceed 20 trillion won by 2030, and it is evaluated as a material with high potential to replace existing graphite-based anodes.
[0006] However, silicon anode materials undergo repeated volume expansion of more than 300% during the charge and discharge process, which generates high mechanical stress and causes problems such as cracking, collapse of the electrode structure, detachment from the current collector, and blockage of the charge transfer path.
[0007] Due to these issues, the commercialization of silicon anode materials is being delayed, and various technological approaches are being taken to resolve this.
[0008] First, there is a method to reduce mechanical stress caused by volume expansion by reducing the size of silicon particles to the nanometer (nm) level. Silicon particles with a size of approximately 150 nm or less have been reported to have low mechanical stress, which reduces breakage during the charging and discharging process; however, the industry points out that there is still a high possibility of breakage occurring with increasing cycles. In addition, toxic substances such as silane (SiH4) gas are used in the manufacturing of nano-silicon, which can lead to environmental problems.
[0009] Another method involves suppressing volume expansion by composites of silicon with silica (SiO2) or graphite-based carbon materials. While silica offers high chemical and mechanical stability, it requires a high-temperature vacuum process for composite formation, and the low silicon ratio limits the capacity increase effect. Additionally, silica causes irreversible reactions with the electrolyte, leading to low initial efficiency. On the other hand, carbon-silicon composites exhibit high initial efficiency but suffer from low cycle life stability due to a lack of structural robustness.
[0010] In addition, there is the development of silicon anode materials based on carbon composites. Research is being conducted on technologies that composite silicon with various commercial carbon sources (graphite, expanded graphite, graphene, CNT, fullerene, carbon black, etc.). However, research on selecting the optimal carbon material is still ongoing, and there is a need to develop an optimized composite structure that can effectively suppress the volume expansion of silicon.
[0011] Currently, silicon anode materials are used by adding them to existing graphite anode materials at a weight ratio of less than 10%, and it is difficult to increase the silicon ratio due to the problem of silicon's high volume expansion. For example, various technical attempts have been made, such as using nanosilicon, synthesizing silicon nanowires, forming composites with silica, and forming carbon composites; however, the cracking phenomenon of silicon has not yet been completely resolved, and it is evaluated that the potential for commercialization is limited due to low sustainability in terms of cost, environment, and energy. Therefore, for the practical application of silicon-based anode materials, it is required to develop technology that can increase the silicon usage ratio while improving initial capacity, and simultaneously improve cycle efficiency and initial efficiency. Additionally, the adhesion between silicon and the carbon material being composited must also be considered important. For example, Korean Registered Patent No. 10-2276657 provides a method for surface-modifying silicon particles with an alkoxysilane-based surface modifier and manufacturing a composite secondary battery anode material containing a graphene-carbon nanotube-silicon composite. The problem to be solved
[0013] The objective of the present invention, devised to solve the problems described above, is to provide a silicon anode material in the form of a composite of functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) with silicon, which has high charging speed, high sphericity, and excellent stability, by first coating the surface of silicon with functionalized graphene (FGO) and second coating with functionalized graphene (FGO) and graphite nanoplatelets (GNP) so that silicon cracking can be suppressed even during repeated charging and discharging of the anode material, thereby having high cycle efficiency, and by optimizing the electron transport path during charging and discharging through the formation of a uniform conductive network on the surface and inside of silicon particles by GNP, which has high electrical conductivity. In particular, by using functionalized graphene (FGO), it is possible to provide a silicon anode material in the form of a composite of functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) with silicon such that the material coated on silicon does not detach and durability and stability can be maintained even under repeated charging and discharging conditions. means of solving the problem
[0015] As a technical means for achieving the technical problem described above, according to one embodiment, a silicon anode material in the form of a composite of functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) with silicon may be provided, comprising: a silicon core; a first coating layer coating functionalized graphene oxide (FGO) on the surface of the silicon core; and a second coating layer coating functionalized graphene oxide (FGO) and graphite nanoplatelet (GNP) on the surface of the first coating layer; wherein the graphite nanoplatelet (GNP) exists in a form impregnated on the surface and inside the silicon core, and the silicon anode material is characterized by having an average particle size of 5 μm or more and 20 μm or less. Effects of the invention
[0017] As described above, the effects of the present invention enable the maintenance of a high silicon content by effectively mitigating the volume expansion problem of silicon through a secondary coating utilizing functionalized graphene oxide (FGO) and graphite nanoplatelets (GNP). Furthermore, by strengthening the adhesion between silicon and carbon materials, it prevents the delamination of the carbon coating layer even during charge-discharge cycles and improves the durability of the composite. In addition, GNP and FGO effectively fill the interior and surface of silicon clusters, thereby increasing electron conductivity and maximizing the performance of silicon-based anode materials. Meanwhile, since the primary and secondary coating processes can be implemented as a single spray-drying process, silicon anode materials in the form of functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) composited with silicon can be efficiently manufactured without complex additional processes. Moreover, the functionalized graphene-based coating layer suppresses the structural collapse of silicon, thereby effectively improving initial efficiency and cycle life. Of course, the scope of the present disclosure is not limited by these effects. Brief explanation of the drawing
[0019] FIG. 1 is a schematic diagram showing the structure of a silicon anode material in which functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) are combined with silicon according to a preferred embodiment of the present invention. FIG. 2 is a flowchart illustrating a method for manufacturing a silicon anode material in which functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) are combined with silicon according to a preferred embodiment of the present invention. FIG. 3 is a diagram showing FGO of a silicon anode material in which functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) are composited with silicon according to a preferred embodiment of the present invention. FIG. 4 is an enlarged view of silicon coated with functionalized graphene oxide (FGO), which is a silicon anode material in the form of a composite of functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) with silicon according to a preferred embodiment of the present invention. FIG. 5 is a diagram showing graphite nanoplatelets (GNP) impregnated on the surface and inside of a silicon anode material in which functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) are composited with silicon according to a preferred embodiment of the present invention. FIG. 6 is an enlarged view of a silicon anode material in which functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) are composited with silicon according to a preferred embodiment of the present invention. Specific details for implementing the invention
[0020] The advantages and features of the present invention and the methods for achieving them will become clear by referring to the embodiments described below in detail together with the accompanying drawings. However, the present invention is not limited to the embodiments disclosed below but may be implemented in various different forms. These embodiments are provided merely to ensure that the disclosure of the present invention is complete and to fully inform those skilled in the art of the scope of the invention, and the present invention is defined only by the scope of the claims. Throughout the specification, the same reference numerals refer to the same components.
[0021] In the following embodiments, terms such as first, second, etc. are used not in a limiting sense, but for the purpose of distinguishing one component from another component.
[0022] In the following examples, singular expressions include plural expressions unless the context clearly indicates otherwise.
[0023] In the following embodiments, terms such as "include" or "have" mean that the features or components described in the specification are present, and do not preclude the possibility that one or more other features or components may be added.
[0024] In the following embodiments, when a part such as a layer, region, or component is described as being on or above another part, it includes not only cases where it is directly on top of another part, but also cases where another region, component, etc. is interposed in between.
[0025] In the drawings, the size of components may be exaggerated or reduced for convenience of explanation. For example, the size and thickness of each component shown in the drawings are depicted arbitrarily for convenience of explanation, and therefore the present disclosure is not necessarily limited to what is depicted.
[0026] In this specification, “A and / or B” indicates the case where it is A, B, or A and B. And, “at least one of A and B indicates the case where it is A, B, or A and B.”
[0027] In the following embodiments, when layers, regions, components, etc. are described as being connected, this includes cases where the layers, regions, components are directly connected, or / or cases where other layers, regions, components are interposed between the layers, regions, components to be indirectly connected. For example, when layers, regions, components, etc. are described as being electrically connected in this specification, it indicates cases where the layers, regions, components, etc. are directly electrically connected, and / or cases where other layers, regions, components, etc. are interposed between them to be indirectly electrically connected.
[0028] Where in this specification a quantity, concentration, or other value or parameter is given as an enumeration of a range, a preferred range, a preferred upper limit, and a preferred lower limit, it should be understood that any pair of any upper range limit or preferred value and any lower range limit or preferred value, regardless of whether the range is disclosed separately, specifically discloses any range that may be formed. Where a range of numerical values is mentioned in this specification, unless otherwise stated, for example, without limiting terms such as greater than or less than, the range is intended to include its endpoint value and all integers and fractions within that range. The scope of the invention is not intended to be limited to the specific value mentioned when defining the range.
[0029] Among the physical properties mentioned in this specification, if the measured temperature affects the property, the property is measured at room temperature unless specifically otherwise specified. The term "room temperature" refers to a natural temperature that has not been heated or cooled, and may mean, for example, any temperature within the range of about 10°C to 30°C, or a temperature of about 23°C or about 25°C. Furthermore, unless specifically otherwise specified, the unit of temperature in this specification is °C.
[0030] In addition, among the physical properties mentioned in this specification, if the measured pressure affects the physical property, unless otherwise specifically defined, the physical property is measured at normal pressure, that is, atmospheric pressure (about 1 atmosphere).
[0031] In this specification, FGO stands for Functionalized Graphene Oxide, which is graphene in which the surface of graphene oxide is modified with functional groups and serves to improve adhesion to the composite material (silicon). GNP stands for Graphite Nanoplatelet, which is a carbon-based nanomaterial having a multilayer graphene structure with high electrical conductivity and mechanical strength. CNT stands for Carbon Nanotube, which is a one-dimensional carbon nanomaterial with high electrical conductivity and mechanical strength and serves to improve the conductivity and durability of the composite through network formation. CB stands for Carbon Black, which is a conductive material composed of fine carbon particles and serves to increase electronic conductivity within the composite and aid in the uniform dispersion of electrodes.
[0033] Hereinafter, the present invention will be described with reference to drawings illustrating silicon in a composite form of functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) with silicon according to embodiments of the present invention.
[0034] FIG. 1 is a schematic diagram showing the structure of a silicon anode material in which functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) are combined with silicon according to a preferred embodiment of the present invention.
[0035] According to one embodiment, a silicon cathode material (10) in the form of a composite of functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) with silicon may include a silicon core (110), a first coating layer (120), and a second coating layer (130).
[0036] For example, the silicon cathode material (10) may include a first coating layer (120) that coats functionalized graphene oxide (FGO) on the surface of a silicon core (100) and a second coating layer (120) that coats functionalized graphene oxide (FGO) and graphite nanoplatelets (GNP) on the surface of the first coating layer.
[0037] According to one embodiment, the silicon cathode material (10) may have an average particle size of 5㎛ or more and 20㎛ or less. By controlling the average particle size so that it does not become too small (less than 5㎛) and does not exceed 20㎛, a suitable specific surface area can be maintained, thereby ensuring both initial efficiency and long lifespan characteristics.
[0038] According to one embodiment, the silicon core (100) is a core active material of the silicon negative electrode material (10), and nano-sized silicon can be formed by gathering several particles to an average of 5㎛ to 20㎛.
[0039] According to one embodiment, the first coating layer (110) may be formed by coating functionalized graphene oxide (FGO) on the surface of a silicon core (100). Various surface functional groups (e.g., -COOH, -OH, epoxy groups, etc.) of the FGO may chemically and physically bond with -SiOH, etc. on the silicon surface to increase adhesion and reduce detachment due to volume expansion.
[0040] According to one embodiment, the second coating layer (120) may be a layer that is composite-coated again on the first coating layer with graphite nanoplatelets (GNP), FGO, and, if necessary, CNT / carbon black (CB). GNP (graphite nanoplatelets) has the characteristic of having high electrical conductivity and mechanical strength.
[0041] More specifically, according to one embodiment, by coating a second coating layer (120), an electron movement path is formed during charging and discharging, and even if the silicon swells due to the impregnation of GNP inside, the effect of preventing structural collapse can be achieved. In addition, FGO can improve the coating layer retention force by making the interfacial bonding between silicon and GNP more robust.
[0042] FIG. 2 is a flowchart illustrating a method for manufacturing a silicon anode material in which functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) are combined with silicon according to a preferred embodiment of the present invention.
[0043] Referring to FIG. 2, a method for manufacturing a silicon cathode material in which functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) are combined with silicon according to the present invention comprises a first spraying liquid manufacturing step (S10), a first drying step (S20), a grinding step (S30), a second spraying liquid manufacturing step (S40), a second drying step (S50), and a heat treatment step (S60).
[0044] First, the first spray solution preparation step (S10) can be prepared by adding and stirring nanosilicon and functionalized graphene oxide (FGO) into a mixed solvent containing an organic solvent and an inorganic solvent.
[0045] Here, the first spray liquid manufacturing step (S10) may include a mixed solvent manufacturing step and a stirring step.
[0046] The mixed solvent preparation step can prepare a mixed solvent comprising at least one organic solvent and at least one inorganic solvent.
[0047] At this time, the mixed solvent may include an organic solvent comprising one or more of ethanol, methanol, and acetic acid, and an inorganic solvent comprising one or more of water, liquid ammonia, and liquid sulfuric acid.
[0048] The organic solvent may be an organic solvent composed of a substance containing carbon (C) bonds, and the inorganic solvent may be an inorganic solvent composed of a substance not containing carbon (C) bonds, but is not limited thereto.
[0049] That is, the mixed solvent can consist of an organic solvent composed of a substance containing carbon (C) bonds and an inorganic solvent that does not.
[0050] In the above mixed solvent, the organic solvent (e.g., ethanol) has high affinity for the surfaces of functionalized graphene oxide (FGO) and nanosilicon, which can help to uniformly disperse FGO and nanosilicon within the solvent. Meanwhile, the inorganic solvent (e.g., water) acts as a polar solvent that promotes physical and chemical reactions and can help ensure stable dispersion of hydrophilic materials such as FGO. That is, compared to using a single inorganic solvent or a single organic solvent in the present invention, using a mixed solvent in which the organic solvent and the inorganic solvent are appropriately mixed can help reduce the phenomenon of nanosilicon and FGO clumping together and enable uniform dispersion, thereby helping to improve the homogeneity of the coating. Furthermore, due to the difference in the volatilization rates of the organic solvent and the inorganic solvent, it is possible to expect an effect of controlling the drying speed while ensuring that nanosilicon and FGO are uniformly coated. In addition, the mixed solvent described above can help improve the adhesion of FGO to the silicon surface by controlling the chemical interaction between FGO and the nanosilicon surface, which can have a positive effect on improving capacitance and cycle efficiency.
[0051] Preferably, the organic solvent in the mixed solvent may include ethanol, and the inorganic solvent may include water, but is not limited thereto. Meanwhile, the inorganic solvent is preferably a polar solvent to ensure high intermolecular forces with FGO and nanosilicon, but is not limited thereto.
[0052] In addition, the organic solvent and the inorganic solvent in the above mixed solvent may be mixed in a mass ratio of 1:1 to 1:5. In other examples, the ratio may be a mass ratio of 1:2, 1:3, or 1:4, but is not limited thereto.
[0053] When the above organic solvent and inorganic solvent are mixed in a mass ratio within the range specified above, the characteristics of the organic solvent and inorganic solvent described above are appropriately exhibited to control the drying speed and help in the uniform coating of FGO and silicon particles.
[0054] Here, if the proportion of organic solvent is excessively high, the high volatility of the mixed solvent can lead to an excessively fast drying speed. Consequently, the solvent evaporates rapidly, making it difficult to achieve uniform dispersion of silicon and functionalized graphene oxide (FGO), and potentially increasing particle aggregation within the coating layer. Furthermore, rapid solvent evaporation causes the coating layer to shrink drastically, increasing residual stress and potentially leading to the formation of fine cracks on the surface of the coating layer. On the other hand, if the proportion of organic solvent is excessively low, the relatively low volatility can result in a slower drying speed and increased processing time. Additionally, poor compatibility with hydrophobic carbon-based materials (such as GNP and CNT) increases the likelihood of the coating layer being formed unevenly.
[0055] The stirring step may involve adding and stirring nanosilicon and functionalized graphene oxide (FGO) to the mixed solvent.
[0056] In this case, the functionalized graphene oxide (FGO) may be graphene oxide with a surface modified and functionalized, and the modified and functionalized functional groups may include, for example, a hydroxyl group (-OH), a carboxyl group (-COOH), an epoxy group (-O-), an amine group (-NH₂), a sulfonate group (-SO₃H), a phosphonate group (-PO₃H₂), a phenyl group (-CH), or two or more of these bonds. The functional groups listed above can play a role in improving the interfacial bonding strength between FGO and silicon, increasing dispersibility, and enhancing electrical and mechanical stability within the composite.
[0057] At this time, the nanosilicon may be 1 to 9 parts by weight per 100 parts by weight of the mixed solvent. In other examples, the above ratio may be 2 parts by weight or more, 3 parts by weight or more, 4 parts by weight or more, or 5 parts by weight or more, or 8 parts by weight or less, 7 parts by weight or less, 6 parts by weight or less, or 5 parts by weight or less, but is not limited thereto.
[0058] When the above-mentioned nanosilicon is mixed in the weight range specified above, the composite can be manufactured without nozzle clogging during the spray drying process while maintaining a high production yield. In other words, if the concentration of nanosilicon is too low, the production yield decreases, which may lower process efficiency; conversely, if it is too high, the viscosity of the solution increases during the spray drying process, making uniform spraying difficult and potentially causing nozzle clogging. Since these issues can ultimately reduce coating uniformity and negatively affect the quality and performance of the composite, it is important to maintain an appropriate concentration of nanosilicon.
[0059] In addition, the nanosilicon may have an average particle size of 0.1 to 0.7 µm. In other examples, the average particle size may be 0.2 or more or 0.3 µm or more, or 0.6 or less, 0.5 or less, or 0.4 µm or less, but is not limited thereto.
[0060] When the nanosilicon has a particle size within the range specified above, the nanosilicon is uniformly dispersed within the mixed solvent, which helps form a uniform coating layer with FGO and GNP, improves the homogeneity of the composite, prevents nozzle clogging, and maximizes the productivity of the spray drying and coating processes. If the nanosilicon has too large a particle size, cracking of the silicon due to volume expansion may occur, and it is difficult to create a stable structure through spray drying. Furthermore, if the nanosilicon has too small a particle size, the specific surface area increases excessively, leading to increased reactivity within the electrode. Consequently, side reactions with the electrolyte increase, which may lower initial efficiency; therefore, it is necessary to select nanosilicon with an appropriate particle size.
[0062] The first drying step (S20) can obtain silicon coated with functionalized graphene oxide (FGO) by spraying and drying the first spray solution.
[0063] At this time, the first spray solution can form silicon coated with FGO on its surface as it dries during spray drying. In addition, a uniform coating layer can be formed on the nanosilicon as the mixed solvent containing organic and inorganic solvents dries at an appropriate rate.
[0064] Silicon inherently has low surface energy and strong chemical inertness, resulting in weak adhesion to general graphene oxide (GO). However, the functionalized graphene oxide (FGO) adopted in the present invention has a modified surface that includes highly affinity functional groups such as carboxyl groups (-COOH), hydroxyl groups (-OH), epoxy groups (-O-), or amine groups (-NH₂). These functional groups can form hydrogen bonds, coordination bonds, or covalent bonds with hydroxyl groups (-Si-OH) on the silicon surface. In particular, strong interfacial bonding between the silicon surface and the functional groups of FGO can be induced through high temperature or appropriate chemical treatment, thereby allowing FGO to be firmly attached to silicon particles. Through the mechanism described above, FGO can effectively bond with the silicon surface to control the volume expansion of silicon and improve structural stability within the electrode.
[0065] The grinding step (S30) allows for the production of silicon powder by grinding the silicon coated with the functionalized graphene oxide (FGO). This enables the silicon particles to be uniformly sized to improve dispersibility, thereby allowing for the formation of a composite with a high specific surface area and uniformity during the subsequent second spray drying process. If the grinding step is omitted, the size of the coated silicon particles may not be uniform, resulting in reduced dispersibility and making it difficult to form a uniform coating layer in subsequent processes. Additionally, if the grinding step is omitted, silicon clusters in an excessively aggregated form may be used as is. Due to this aggregation, internal stress may concentrate during the charging and discharging process, leading to easy cracking, which can result in reduced electrode lifespan and performance degradation.
[0066] The second spray liquid manufacturing step (S40) can be performed by adding and stirring the silicon powder, graphite nanoplatelets (GNP), and binder polymer to produce the second spray liquid.
[0067] In other words, the second spray solution manufacturing step (S40) is a process of preparing a uniform second spray solution by adding graphite nanoplatelets (GNP) and a binder polymer to crushed silicon powder. In this step, GNP forms a conductive network to improve the electrical conductivity of silicon and mitigates the volume expansion of silicon during charging and discharging. In particular, it has been experimentally confirmed that GNP contributes significantly to improving the capacitance and cycle efficiency of the composite. Additionally, the binder polymer strengthens the bonding force between silicon and GNP to increase the structural stability of the composite and can induce the formation of a uniform spherical composite during the subsequent spray drying process. That is, the second spray solution prepared through this process can play an important role in forming a silicon anode material in the form of a composite of silicon with functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) during the spray drying step described later.
[0068] At this time, the binder polymer may be, for example, PVDF, PVA, CMC, or a combination of two or more of these, but is not limited thereto.
[0069] Additionally, the second spray liquid preparation step (S40) may involve adding carbon nanotubes (CNT) and carbon black (CB) and stirring. CNTs have a one-dimensional nanostructure and provide high electrical conductivity and mechanical strength, forming a conductive network within a silicon anode material in which functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) are composited with silicon, and optimizing the electron movement path during charging and discharging. CB (carbon black) consists of fine carbon particles that can perform the function of improving electrical conductivity within the electrode and strengthening interfacial bonding between silicon and GNP. When CNTs and CB are added and stirred in an appropriate ratio at this step, silicon, GNP, CNTs, and CB are uniformly dispersed, and the electrochemical performance of the composite can be significantly improved. In particular, CB can reduce contact resistance within the electrode through uniform distribution, improve electron mobility by securing conductive paths, and maintain the structural stability of the electrode during charging and discharging cycles. In addition, GNP provides high electrical conductivity through its multilayer graphene structure, and CNT can improve mechanical strength by forming a conductive network due to its one-dimensional nanostructure. Therefore, when GNP, CNT, and CB are mixed together in a composite, a synergistic effect can be expected in which electrical conductivity and mechanical stability are simultaneously enhanced.
[0070] In addition, the sum of the masses of graphite nanoplatelets (GNP), carbon nanotubes (CNT), and carbon black (CB) added to the second spray solution may be less than or equal to twice the mass of the binder polymer. The range of the sum of the masses may be, for example, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, or 1.5 times or less, but is not limited thereto, and may be 0.5 times or more. The mass ratio specified above is intended to optimize the mechanical stability and electrical properties of the composite by maintaining an appropriate balance between the conductive carbon material and the binder within the electrode. If the sum of the masses of GNP, CNT, and CB exceeds twice the mass of the binder polymer, the carbon material becomes excessive, weakening the bonding force between particles within the electrode, and the binder may not function sufficiently, which may lead to a decrease in the mechanical strength of the electrode. In particular, since volume expansion occurs during the charge and discharge process in silicon-based anode materials, if the proportion of carbon material is too high, the binder may not be able to sufficiently hold the silicon particles, which can lead to a decrease in the stability of the electrode structure and cause a decline in charge-discharge performance and cycle efficiency. Meanwhile, if the sum of the masses of GNP, CNT, and CB is lowered to less than 0.5 times the binder polymer, the formation of a conductive network within the electrode becomes incomplete, resulting in reduced electrical conductivity and impaired electron mobility, which may lead to a decrease in electrode performance. Additionally, if the amount of CB or CNT is too small, electrode stability during charge-discharge cycles is reduced, and long-term lifespan characteristics may be degraded. Therefore, by maintaining the mass ratio specified above, it is possible to select an optimal composition ratio that simultaneously satisfies high electrical conductivity and charge-discharge characteristics while maintaining the structural stability of the silicon anode material in which functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) are composited with silicon.
[0071] In addition, the graphite nanoplatelets (GNP) may be included in an amount of 0.5 to 2 parts by weight per 100 parts by weight of the second liquid, preferably in an amount of 1 part by weight, but are not limited thereto.
[0072] In addition, the carbon nanotubes (CNT) may be included in an amount of 0.5 to 2 parts by weight per 100 parts by weight of the second liquid, preferably in an amount of 1 part by weight, but are not limited thereto.
[0073] In addition, the carbon black (CB) may be included in an amount of 0.5 to 2 parts by weight per 100 parts by weight of the second liquid, preferably in an amount of 1 part by weight, but is not limited thereto.
[0074] Since GNP, CNT, and carbon black (CB) play a role in forming a conductive network within the composite, their proportions need to be appropriately controlled. If their proportions are too high, the carbon content within the electrode increases excessively, which may reduce the capacitance of the silicon composite and cause carbon to detach from the composite during the charging and discharging process. Conversely, if the proportions are too low, the conductive network is not sufficiently formed, hindering electron movement and consequently reducing the electrical conductivity of the electrode. Therefore, the weight ratio of GNP, CNT, or carbon black can be designed to simultaneously ensure electrical conductivity and mechanical stability by maintaining the ratios specified above.
[0075] In addition, the binder polymer may be included in an amount of 0.5 to 2 parts by weight per 100 parts by weight of the second liquid, preferably 5 parts by weight, but is not limited thereto. If the concentration of the binder polymer is too low, the formulation of the secondary composite may not be properly formed, which may reduce the structural stability of the electrode and weaken the bonding force between the silicon and carbon materials within the composite. Conversely, if the concentration of the binder polymer is too high, the proportion of inactive components within the electrode increases, which may reduce the capacitance of the silicon anode material in the form of a composite of silicon with manufactured functionalized graphene (FGO) and GNP (Graphite NanoPlatelet). Therefore, by maintaining the weight ratio of the binder polymer at the ratio specified above, it is possible to secure the mechanical stability of the composite while maintaining a high energy storage capacity.
[0076] In addition, the silicon powder added to the second spray solution may be included in an amount of 1 to 9 parts by weight per 100 parts by weight of the second spray solution. In other examples, the weight ratio of the silicon powder may be 2 or more, 3 or more, 4 or more, or 5 or more, or 8 or less, 7 or less, 6 or less, or 5 or less, but is not limited thereto. If the content of the silicon powder is lower than the range specified above, the high capacity characteristics of silicon cannot be fully utilized, and the energy storage capacity of the electrode may decrease. On the other hand, if the content of the silicon powder exceeds the range specified above, the volume expansion of silicon increases excessively, which lowers the mechanical stability of the electrode during the charge and discharge process and increases side reactions with the electrolyte, which may shorten the cycle life. Therefore, in the present invention, by controlling the content of the silicon powder added to the second spray solution to within the range specified above, the mechanical stability, electrochemical performance, and long-term cycle life of the electrode can be optimized while maintaining the high capacity characteristics of silicon.
[0077] The second drying step (S50) involves spraying and drying the second spray liquid to obtain a silicon cathode material in the form of a composite of functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) with silicon.
[0078] At this time, the spraying and drying steps may be applied in the same manner as the first drying step described above, but there may be a difference in that the second spraying liquid additionally includes carbon-based materials such as GNP in addition to FGO. In this drying step, a carbon coating layer may be formed secondarily on the surface and inside of the silicon powder coated with FGO first.
[0079] This step is designed to form an additional carbon layer in a single process by mixing silicon powder, FGO, and GNP into a spray drying liquid without the need for a separate individual coating process. This simplifies the process and enables high-volume processing, thereby significantly improving economic and time efficiency.
[0080] In this case, FGO enhances the stability of the carbon layer by strengthening adhesion to silicon, while GNP acts as a crosslinker to effectively bond to the surface of the silicon powder. Additionally, GNP forms a conductive network together with FGO not only on the surface of the silicon powder but also within it, thereby improving the electrical conductivity of the composite and contributing to the improvement of charge and discharge performance.
[0081] The structure of a silicon anode material in which functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) formed through this step are composited with silicon is shown in Fig. 5.
[0082] The heat treatment step (S60) is a step for stabilizing the carbon coating layer described above, in which a silicon anode material in the form of a composite of functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) with silicon is heat-treated in an inert atmosphere.
[0083] That is, the heat treatment step (S50) can increase the bonding strength between silicon, FGO, and GNP, so the expansion of silicon powder can be suppressed. Accordingly, referring to FIG. 4, a silicon anode material in which heat-treated functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) are composited with silicon can be seen.
[0084] Specifically, the heat treatment step (S60) can be performed for 2 to 4 hours in an inert atmosphere at 600 to 800°C.
[0085] That is, if heat treatment is performed at 600 to 800°C, the remaining organic components, such as binder polymer and organic solvent, are effectively carbonized, and a conductive carbon coating layer can be formed.
[0086] At this time, if the temperature is 600°C or lower, carbonization of the organic components does not occur, and the carbon coating layer may be formed unevenly, and if the temperature is 800°C or higher, mass loss may occur due to deterioration.
[0087] In addition, if the heat treatment time is 2 hours or less, carbonization may not be completely achieved, resulting in the formation of an uneven carbon coating layer, and if it is 4 hours or more, the strength may decrease due to deterioration.
[0088] Meanwhile, the present invention has one objective of providing a silicon anode material in which the functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) described above are composited with silicon.
[0089] In addition, the present invention can provide a silicon anode material comprising a silicon core, a primary coating layer coated on the silicon core and comprising functionalized graphene oxide (FGO), and a secondary coating layer coated on the primary coating layer and comprising functionalized graphene oxide (FGO) and graphite nanoplatelets (GNP), wherein the graphite nanoplatelets (GNP) are impregnated on the surface and inside the silicon core and have an average particle size of 5 to 20 μm, and the functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) are composited with silicon.
[0090] Specifically, the silicon anode material in the form of a composite of functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) manufactured according to the present invention with silicon may include a core composed of silicon, and a primary coating layer in which functionalized graphene oxide (FGO) is coated on the silicon core may be formed. A secondary coating layer in which FGO and GNP are additionally coated may be formed on the primary coating layer.
[0091] Through this structure, the FGO of the primary coating layer can improve the durability of the coating by forming a strong interfacial bond with silicon, and the GNP of the secondary coating layer can increase the electrical conductivity of the composite by forming a conductive network. In addition, since the GNP is impregnated not only on the surface but also inside the silicon core, it can effectively mitigate the volume expansion of silicon during the charging and discharging process and ensure the structural stability of the electrode.
[0092] In addition, the present invention provides a silicon anode material in which functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) having an average particle size of 5 to 20 μm are composited with silicon, thereby inducing uniform dispersion among particles within the electrode and improving the charge / discharge efficiency and cycle life of the silicon-based anode material. The average particle size may be 7 or more, 9 or more and 11 μm or more, or 18 or less, 16 or less, or 14 μm or less, but is not limited thereto.
[0093] Meanwhile, the present invention can provide a secondary battery comprising a silicon anode material in which the functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) prepared above are composited with silicon. The battery can be expected to significantly improve the driving range of a vehicle, reduce charging time, and extend battery life.
[0095] The advantages and features of the present invention and the methods for achieving them will become clear by referring to the embodiments described below in detail together with the accompanying drawings. However, the present invention is not limited to the embodiments disclosed below but may be implemented in various different forms. These embodiments are provided merely to ensure that the disclosure of the present invention is complete and to fully inform those skilled in the art of the scope of the invention, and the present invention is defined only by the scope of the claims. Throughout the specification, the same reference numerals refer to the same components.
[0096] Hereinafter, the present invention will be described with reference to the drawings illustrating a method for manufacturing a silicon anode material in which functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) are composited with silicon according to embodiments of the present invention.
[0098] [Example 1]
[0099] First, nanosilicon is prepared by grinding silicon with a diameter of 1 µm to a diameter of 0.3 µm using a ball mill or jet mill.
[0100] Then, a mixed solvent is prepared by mixing water and ethanol in a 1:1 mass ratio. Subsequently, the above nanosilicon is added to the mixed solvent at 5 wt%, and functionalized graphene oxide (FGO) is added at approximately 1 wt%, and then stirred at room temperature to prepare a first spray solution.
[0101] Additionally, the prepared first spray solution is spray-dried to obtain silicon coated with functionalized graphene oxide (FGO). The spray-drying process can be carried out in a manner that induces a uniform FGO coating on individual silicon particles as the solution sprayed in the form of fine droplets dries rapidly. Subsequently, the obtained silicon is sufficiently dried and ground using a ball mill to produce silicon powder.
[0102] Subsequently, 1 wt% of GNP, 5 wt% of binder polymer, 1 wt% of CNT, and 1 wt% of carbon black are each added to a water solvent to prepare a second spray solution, and the silicone powder is added in an amount of 5 parts by weight relative to 100 parts by weight of the second spray solution and stirred thoroughly.
[0103] The prepared second spray solution is spray-dried to obtain a silicon cathode material in which functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) are composited with silicon.
[0104] The silicon anode material in which the above functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) are composited with silicon is heat-treated at 700°C in an inert atmosphere for 3 hours.
[0105] In this way, a silicon anode material is manufactured by combining functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) with silicon.
[0106] It was confirmed that the silicon anode material, in which the finally manufactured functionalized graphene (FGO) and graphite nanoplatelets (GNP) are composited with silicon, comprises a silicon core, a primary coating layer containing functionalized graphene oxide (FGO), and a secondary coating layer containing functionalized graphene oxide (FGO), graphite nanoplatelets (GNP), carbon nanotubes (CNT), and carbon black (CB). Additionally, it was confirmed through Figures 3 to 5 that graphite nanoplatelets (GNP) exist impregnated not only on the surface of the particles but also inside, and the average particle size was measured to be approximately 8 to 12 μm.
[0108] [Comparative Example 1]
[0109] Comparative Example 1 is prepared by not adding functionalized graphene oxide (FGO) and omitting the first drying step in the preparation of the first spray solution of Example 1.
[0111] [Comparative Example 2]
[0112] Comparative Example 2 is prepared without adding graphite nanoplatelets (GNP) in the preparation of the second spray solution of Example 1.
[0114] [Comparative Example 3]
[0115] Comparative Example 3 is prepared by using a water solvent (single solvent) instead of a mixed solvent in the preparation of the first spray solution of Example 1.
[0117] [Comparative Example 4]
[0118] Comparative Example 4 is prepared in the same manner as Example 1, but with the heat treatment step omitted.
[0120] [Comparative Example 5]
[0121] Comparative Example 5 is prepared in the same manner as Example 1, but with 1 μm microsilicon instead of 0.3 μm nanosilicon.
[0123] [Evaluation Example]
[0124] The composite cathode material of Example 1 and the cathode materials of Comparative Examples 1 to 5 were appropriately mixed with spherical graphite for cathode materials, and then an aqueous dispersion of the mixture was prepared by mixing it with an appropriate amount of water, a binder (SMC / CBR or PAA is suitable), and a conductive material (carbon black such as SuperP), and then coated onto a copper electrode plate. Subsequently, heat treatment was performed to ensure the mixture was firmly coated onto the copper electrode plate, and then stamped to produce a circular cathode electrode plate. In addition, a lithium chip was prepared as the anode plate, and a PE separator, a spacer, a coin cell container, a spring, and a gasket were prepared and combined to manufacture a coin cell. The capacitance (mAh / g) and cycle efficiency (200 cycles, %) of the manufactured coin cell were measured under 0.1C / 0.1C charge / discharge conditions at 25°C, and the results are shown in Table 1.
[0125] The experimental results regarding the capacitance and cycle efficiency for the above-described Example 1 and Comparative Examples 1 to 5 are as shown in [Table 1] below.
[0126] Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Storage capacity (mAh / g) 2,002 1,912 1,822 1,544 1,716 2,179 Cycle efficiency (200 cycle, %) 94 85 83 85 79 74
[0127] Referring to [Table 1], it can be confirmed that the silicon anode material in which functionalized graphene (FGO) and GNP (Graphite NanoPlatelet) according to Example 1 are composited with silicon exhibits superior capacitance and cycle efficiency compared to the anode materials of Comparative Examples 1 to 5. Specifically, in the case of Comparative Example 1, which did not contain FGO, a tendency for both capacitance and cycle efficiency to decrease was observed compared to Example 1. This suggests that the absence of FGO weakens the adhesion between the carbon coating layer and the silicon core, causing delamination during the charging and discharging process, which in turn lowers the structural stability of the electrode. In the case of Comparative Example 2, which did not contain GNP, it can be inferred that the conductivity within the electrode decreases, leading to an increase in internal resistance. Consequently, electron movement during the charging and discharging process is not smooth, resulting in increased reaction resistance of the electrode; it was confirmed that both capacitance and cycle efficiency decreased compared to Example 1. Comparative Example 3, prepared using a single solvent rather than a mixed solvent, showed a significant decrease in capacitance compared to the Example. This is presumed to be because the aggregation of the carbon electrode active material became severe and was not uniformly dispersed, leading to a decrease in the homogeneity of the coating layer and consequently an increase in local resistance during the charge-discharge process. This is because if the coating layer is not uniform, the electron movement path is not formed evenly. Comparative Example 4, which omitted the heat treatment step, was not effectively carbonized by the remaining binder polymer and organic components of the organic solvent, resulting in an incomplete formation of a conductive carbon coating layer. Consequently, it is predicted that the capacitance and cycle efficiency decreased compared to the Example. Comparative Example 5, which used microsilicon (1 μm) instead of nanosilicon, showed a slight increase in initial capacitance compared to Example 1, but exhibited a tendency for cycle efficiency to decrease significantly. This is presumed to be because as the size of the microsilicon particles increases, volume expansion intensifies during the charge-discharge process, and the mechanical stability of the electrode decreases.In particular, it is analyzed that repeated charging and discharging causes silicon particles to crack rapidly, disrupting the conductive network within the electrode and accelerating the delamination of the electrode active material, which significantly reduces long-term cycle efficiency. Therefore, it can be confirmed that the composite anode material produced by the manufacturing method of the present invention exhibits excellent performance in both capacitance and cycle efficiency, and it is expected to have high potential to be utilized as a next-generation anode material technology in the future electric vehicle battery market.
[0129] A person skilled in the art to which the present invention pertains will understand that the present invention may be implemented in other specific forms without altering its technical concept or essential features. Therefore, the embodiments described above should be understood as illustrative in all respects and not restrictive. The scope of the present invention is defined by the claims set forth below rather than by the detailed description above, and all modifications or variations derived from the meaning and scope of the claims and their equivalents should be interpreted as being included within the scope of the present invention. Furthermore, the order of operation of the configurations described in the above process does not necessarily need to be performed in a chronological order, and it is understood that even if the order of execution of each configuration and step is changed, such a process may fall within the scope of the present invention as long as it satisfies the essence of the present invention. Explanation of the symbols
[0131] S10: First spray liquid manufacturing step S20: First drying step S30: Grinding stage S40: Second spray liquid manufacturing step S50: Second drying stage S60: Heat treatment step
Claims
Claim 1 A silicon anode material in the form of a composite of functionalized graphene (FGO) and graphite nanoplatelets (GNP) with silicon, comprising: a silicon core; a first coating layer coating functionalized graphene oxide (FGO) on the surface of the silicon core; and a second coating layer coating functionalized graphene oxide (FGO) and graphite nanoplatelets (GNP) on the surface of the first coating layer; wherein the graphite nanoplatelets (GNP) exist in a form impregnated on the surface and inside the silicon core, and the silicon anode material is characterized by having an average particle size of 5 μm or more and 20 μm or less. Claim 2 A silicon anode material according to claim 1, wherein the nanosilicon for forming the silicon core comprises nanosilicon having an average particle size of 0.1 μm or more and 0.7 μm or less, and to form the core of the nanosilicon, a solvent is used in which an organic solvent comprising one or more of ethanol, methanol, and acetic acid is mixed with an inorganic solvent comprising one or more of water, liquid ammonia, and liquid sulfuric acid in a mass ratio of 1:1 to 1:5, and a first coating layer is formed on the nanosilicon through functionalized graphene oxide (FGO) coating by adding 1 to 9 parts by weight of nanosilicon to 100 parts by weight of the solvent, and silicon powder is prepared by grinding the nanosilicon having the first coating layer formed thereon. Claim 3 A silicon anode material according to claim 2, wherein the secondary coating layer is formed by adding graphite nanoplatelets (GNP), carbon nanotubes (CNT), and / or carbon black (CB) together with a binder polymer to the silicon powder, and wherein the silicon powder having the secondary coating layer formed thereon is characterized in that the sum of the masses of the graphite nanoplatelets (GNP), carbon nanotubes (CNT), and carbon black (CB) is less than or equal to twice the mass of the binder polymer. Claim 4 A silicon anode material according to claim 3, characterized in that the silicon powder having the secondary coating layer formed thereon is heat-treated in an inert atmosphere at 600°C or higher and 800°C or lower for 2 hours or more and 4 hours or less, thereby having a structure in which the primary coating layer and the secondary coating layer are each stabilized and bonded.
